2020
DOI: 10.3389/fpsyg.2020.01601
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Modeling of Drivers’ Situation Awareness Considering Road and Driver Factors

Abstract: Driver's situation awareness (SA) is one of the key elements that affect driving decisionmaking and driving behavior. SA is influenced by many factors, and previous studies have focused only on individual factors. This study presents a comprehensive study to explore the path relationships and influence mechanism between SA and all influential factors, including road characteristics, driver characteristics and states, distracting elements, and cognitive ability. A structural equation model that relates SA to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A crucial construct, which has been identified as a significant predictor of successful driving [52], is situational insight or situation awareness [53], in which both the assumptions of a standard TPE (such as intelligence or attention) and driving experience are involved. SA is commonly discussed in highly specialized areas such as air traffic control [54], military activities [55,56], remotely controlled vehicles operation [57] and it is also directly studied in the context of virtual car driving [58,59].…”
Section: Cognitive Measures Crucial For Drivingmentioning
confidence: 99%
See 3 more Smart Citations
“…A crucial construct, which has been identified as a significant predictor of successful driving [52], is situational insight or situation awareness [53], in which both the assumptions of a standard TPE (such as intelligence or attention) and driving experience are involved. SA is commonly discussed in highly specialized areas such as air traffic control [54], military activities [55,56], remotely controlled vehicles operation [57] and it is also directly studied in the context of virtual car driving [58,59].…”
Section: Cognitive Measures Crucial For Drivingmentioning
confidence: 99%
“…Smith and Hancock emphasize that both the processes of perception and the processes of memory and situational awareness are externally focused consciousness that creates knowledge about the current situation [64]. Situational insight thus represents a key category within TPE since previous studies suggested that a driver's SA is crucial for decision-making and behavior in driving [52]. Concurrently, they emphasized that SA is influenced by several basic factors, which were, actually, usually only studied separately.…”
Section: Cognitive Measures Crucial For Drivingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have studied essential driver characteristics, such as driver sleepiness (Resalat and Saba, 2015 ), drowsiness (Lin et al, 2005 ), fatigue (Jap et al, 2009 ; Arakawa et al, 2019 ), alertness level (Kiymik et al, 2004 ), and cognitive load (Barua et al, 2017 ). Other studies have used EEG, as the effect of color scheme (Yang et al, 2020a ), situation awareness (Yang et al, 2020b ), and the effect of directional signs (Yang et al, 2020c ). Other studies on brain activities, driver aggressiveness, music and emotion, and EEG classification have also been conducted (Fan et al, 2010 ; Liu et al, 2013 ; Lin et al, 2014 ; Yang et al, 2018 , 2019a ; Zeng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%